An open label randomised controlled trial to assess the effect of Harishadi Ghana Vati & Virechan Karma in the management of Tamaka Shwasa vis-a-vis Bronchial asthma - Nitin; Abhinav; Prasad, Rajendra (International Research Journal of Ayurveda & Yoga, 2021)
Background: Bronchial asthma, characterised by chronic bronchial hyperactivity and varying degrees of obstruction, is one among the leading causes of respiratory deaths across the globe. Tamaka Shwasa, a variant of Shwasa Roga bears resemblance with bronchial asthma in its symptoms. Ayurveda offers an array of Shodhana (Purification) and Shamana (Pacification) procedures for effective management of Tamaka swasa (bronchial asthma), which can be applied in the former disease too. Aim: The present study is aimed to evaluate the efficacy of Harishadi Ghana Vati and Virechana karma in the management of Tamaka Shwasa (Bronchial Asthma). Materials and methods: 63 patients were enrolled randomly in three groups A, B and C, irrespective of their genders, between the age group of 30-60 years, with confirmed diagnosis of Bronchial Asthma. Out of which, 60 patients completed the trial with Harishadi Ghana Vati 500 mg TDS for 2 months, individually in Group A and after Virechana Karma (Purgation) in group B, Doxofylline 400 mg OD in group C. Change in the grading of complaints and mean values pulmonary function test (PFT) from their baseline value were studied as the primary outcome. Results: Group B has highly significant clinical improvement with all safety profile in comparison to group C. Conclusion: significant clinical improvement was found in group B as compared to other groups